(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Zlatnikov V. H. Teaching cadets of higher military educational institutions professionally-oriented listening comprehension. The paper highlights the role of foreign language communication in the professional activity of the future officers of the Armed Forces of Ukraine; the features of cadets’ training of professionally-oriented listening comprehension are considered. The main difficulties of listening comprehension of military terminology are analyzed.